Normativity in Comparative Religious Ethics - Jung, Kevin (Journal of religious ethics, 2017)
This essay seeks to clarify the meaning and nature of normativity in metaethics and offers reasons why comparative religious ethics (CRE) must properly address questions about normativity. Though many comparative religious ethicists take CRE to be a normative discipline, what they say about normativity is often unclear and confusing. I argue that the third-wave scholars face serious questions with respect to not only the justification of moral belief but also the rationality of moral belief and action. These scholars tend to view the justification of moral belief to be a matter of process (that is, discursive social practice) rather than evidence-possession, thus overlooking crucial differences between the two. They also run the risk of confusing motivating and explanatory reasons with normative reasons for moral belief and action. Consequently, their account of normativity would be insufficient for determining the rationality of moral beliefs and actions as well as for justifying moral beliefs.